2015
DOI: 10.1111/bjd.13489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological features of head and neck melanoma: a population-based study in France

Abstract: HNMs highly differ from MOS, and are clinically and histologically heterogeneous, possibly as a consequence of different patterns of sun exposure. These data could help to improve primary and secondary prevention messages for patients and doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 48 publications
(74 reference statements)
9
36
1
Order By: Relevance
“…Clinically, compared with melanoma of other skin sites, HNM, particularly scalp melanoma, is more aggressive and have an overall poorer prognosis, which may be partly explained by a late diagnosis due to hidden by hair . Our findings may also be partly attributed to the timely diagnosis among balding men compared with non‐balding men.…”
Section: Discussionmentioning
confidence: 64%
“…Clinically, compared with melanoma of other skin sites, HNM, particularly scalp melanoma, is more aggressive and have an overall poorer prognosis, which may be partly explained by a late diagnosis due to hidden by hair . Our findings may also be partly attributed to the timely diagnosis among balding men compared with non‐balding men.…”
Section: Discussionmentioning
confidence: 64%
“…In general, trunk melanomas are more common in younger patients and head and neck melanomas occur in older patients(Dabouz et al, ). Long‐term UV exposure may lead to DNA damage over time that perpetuates development of different histologic subtypes (i.e., Lentigo Maligna Melanoma, LMM; Dabouz et al, ; Gillgren et al, ; Thorn, Adami, Ringborg, Bergstrom, & Krusemo, ). We found that trunk and extremity melanomas were associated with decreased melanoma‐specific mortality in the older age‐group in the multivariable analysis ( p ‐value = 0.007 for trunk and p ‐value = 0.05 for extremities) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, case 2 in our study was initially diagnosed as nodular melanoma. The nodular subtype of melanoma appears to be overrepresented among the melanomas arising in the head and neck (20% vs. 12% at other sites) . Nodular melanomas may lack a radial growth phase and show a nested growth pattern, like clear cell sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The nodular subtype of melanoma appears to be overrepresented among the melanomas arising in the head and neck (20% vs. 12% at other sites). 18 Nodular melanomas may lack a radial growth phase and show a nested growth pattern, like clear cell sarcoma. In addition, melanomas with clear cell morphology are described, which may add to diagnostic confusion.…”
Section: Discussionmentioning
confidence: 99%